2013
DOI: 10.1063/1.4829912
|View full text |Cite
|
Sign up to set email alerts
|

Shape evolution of high aspect ratio holes on Si(001) during hydrogen annealing

Abstract: We study the dynamics of void formation through the shape evolution of high-aspect-ratio cylindrical holes in Si(001) substrates under hydrogen annealing. We compare the observed evolution of these holes with numerical simulations based on the continuum theory for surface-diffusion-driven shape evolution. We find that a strong morphological instability arises near the hole opening, regardless of the presence of anisotropy in surface energy. The observed shape evolution of high-aspect-ratio holes during hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…The present authors have used the tangential degrees of freedom to improve the mesh quality during the evolution of discretized curvature flows, see [2,3,4,5]. There has been interest in numerical schemes for axisymmetric schemes for geometric evolution equations both for second and for fourth order flows, see [41,40,14,19,20,23,25,44,47]. However, the literature on numerical analysis of such schemes is sparse.…”
Section: Introductionmentioning
confidence: 99%
“…The present authors have used the tangential degrees of freedom to improve the mesh quality during the evolution of discretized curvature flows, see [2,3,4,5]. There has been interest in numerical schemes for axisymmetric schemes for geometric evolution equations both for second and for fourth order flows, see [41,40,14,19,20,23,25,44,47]. However, the literature on numerical analysis of such schemes is sparse.…”
Section: Introductionmentioning
confidence: 99%
“…As illustrated in Figures f and g, Si NPs can be transformed into two types of SON structures, depending on the AR of the initial Si NPs. For instance, Sato et al demonstrated that when the AR of initial Si NPs is larger than 3, Si NPs reorganize to a Si film on spherical-shaped voids upon annealing (Figure f). If the initial pores have an AR < 3, the surface is simply flattened by surface diffusion.…”
Section: Resultsmentioning
confidence: 99%
“…Fatigue in Si attracts much attention in the MEMS community because many of Si MEMS mechanical elements are subjected to cyclic stressing [36][37][38][39][76][77][78][79][80][81][82][83][84]. Kamiya et al [78] did a Round Robin test to examine the S-N curve for Si.…”
Section: Siliconmentioning
confidence: 99%
“…Fatigue in Si attracts much attention in the MEMS community because many of Si MEMS mechanical elements are subjected to cyclic stressing [36–39,76–84]. Kamiya et al .…”
Section: Materials Characteristicsmentioning
confidence: 99%